2015
DOI: 10.1186/s13601-015-0045-z
|View full text |Cite
|
Sign up to set email alerts
|

Health economic comparison of SLIT allergen and SCIT allergoid immunotherapy in patients with seasonal grass‐allergic rhinoconjunctivitis in Germany

Abstract: BackgroundAllergoids are chemically modified allergen extracts administered to reduce allergenicity and to maintain immunogenicity. Oralair® (the 5-grass tablet) is a sublingual native grass allergen tablet for pre- and co-seasonal treatment. Based on a literature review, meta-analysis, and cost-effectiveness analysis the relative effects and costs of the 5-grass tablet versus a mix of subcutaneous allergoid compounds for grass pollen allergic rhinoconjunctivitis were assessed.MethodsA Markov model with a time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(76 citation statements)
references
References 39 publications
2
74
0
Order By: Relevance
“…Some studies have been previously shown levels of IL-10 significantly increased in the sera or cutaneous samples of patients with CSU, compared with the healthy population which is consistent with our data [26]. By contrast, some other studies discovered patients with CSU had lower serum levels of IL-10 compared with the healthy population [27]. …”
Section: Discussionsupporting
confidence: 92%
“…Some studies have been previously shown levels of IL-10 significantly increased in the sera or cutaneous samples of patients with CSU, compared with the healthy population which is consistent with our data [26]. By contrast, some other studies discovered patients with CSU had lower serum levels of IL-10 compared with the healthy population [27]. …”
Section: Discussionsupporting
confidence: 92%
“…Two of these studies are included separately in both asthma and rhinitis analyses. Nineteen studies focussed on allergic rhinitis, three on asthma and one on venom allergy . No studies were identified investigating the cost‐effectiveness of food allergy.…”
Section: Resultsmentioning
confidence: 99%
“…The overall quality of the studies was low. Of the 19 allergic rhinitis studies, nine were assessed to be of low quality, six medium and four high quality . Of the three asthma studies, two were of a low quality and one high quality .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[209][210][211][212] Seven studies based on RCT data conducted from a health system perspective and using QALYS as their outcome measure suggests that SLIT and SCIT would be considered cost-effective in this patient population in United Kingdom at the standard National Institute for Health and Care Excellence (NICE) cost-effectiveness threshold of £20 000 (€24 616) per QALY. [213][214][215][216][217][218][219] The studies comparing SCIT and SLIT have given mixed results and do not allow us to conclude whether either treatment is more cost-effective. 220 ICERs for cost evaluations of AIT seem to vary substantially between different health systems suggesting that straightforward conclusions may not be generalizable even across seemingly similar countries.…”
Section: Pharmacoeconomic Aspe Cts Of Ait Versus Pharmacothe Rapy Fmentioning
confidence: 99%